Individualized positive end-expiratory pressure reduces driving pressure in obese patients during laparoscopic surgery under pneumoperitoneum: a randomized clinical trial - Xavier, Tiago Batista; Coelho, Leonardo Vicente; Ferreira, Daniel Antonio Lopes; Cota y Raposeiras, José Manuel; Duran, Marcelo Sampaio; Silva, Leticia Almeida; Motta-Ribeiro, Gabriel Casulari da; Camilo, Luciana Moisés; Carvalho, Alysson Roncally Silva; Silva, Pedro Leme (Frontiers in Physiology, 2024)
INTRODUCTION: During pneumoperitoneum (PNP), airway driving pressure (DP,RS) increases due to stiffness of the chest wall and cephalic shift of the diaphragm, which favors atelectasis. In addition, depending on the mechanical power (MP) formulas, they may lead to different interpretations. METHODS: Patients >18 years-of-age with body mass index >35 kg/m2 were included in a single-center randomized controlled trial during bariatric surgery by abdominal laparoscopy. Intra-abdominal pressure was set at 15 mmHg at pneumoperitoneum timepoint (PNP). After recruitment maneuver, the lowest respiratory system elastance (E,RS) was detected during PEEP step-wise decrement. Patients were randomized to: (1) CTRL: ventilated with PEEP of 5 cmH2O; (2) PEEPIND: ventilated with PEEP value associated with E,RS 5% higher than its lowest level. Respiratory system mechanics and mean arterial pressure (MAP) were assessed at PNP, 5 min after randomization (T1) and at the end of the ventilation protocol (T2); arterial blood gas was assessed at PNP and T2. DP,RS was the primary outcome. Three MP formulas were used: MPA, which computes static PEEP × volume, elastic, and resistive components; MPB, which computes only the elastic component; MPC, which computes static PEEP × volume, elastic, and resistive components without inspiratory holds. RESULTS: Twenty-eight patients were assessed for eligibility; 8 were not included and 20 patients were randomized and allocated to CTRL and PEEPIND groups (n=10/group). The PEEPIND ventilator strategy reduced DP,RS compared with CTRL group (PEEPIND, 13±2 cmH2O; CTRL, 22±4 cmH2O; p<0.001). Oxygenation improved in PEEPIND group compared with CTRL group (p=0.029), whereas MAP was comparable between PEEPIND and CTRL groups. At end of surgery, MPA and MPB were correlated in both CTRL (rho=0.71, p=0.019) and PEEPIND (rho=0.84, p=0.020) groups, but showed different bias (CTRL, −1.9 J/min; PEEPIND, +10.0 J/min). At the end of surgery, MPA and MPC were correlated in both CTRL (rho=0.71, p=0.019) and PEEPIND (rho=0.84, p=0.020) groups, but showed different bias (CTRL, −1.9 J/min; PEEPIND, +10.0 J/min). CONCLUSION: Individualized PEEP was associated with a reduction in DP,RS and improvement in oxygenation with comparable MAP. The MP which solely computes the elastic component better reflected the improvement in DP,RS observed in individualized PEEP group.